Salvatore Quasimodo, word in the lightning and the history (Iter, 2022)
This present essay is about thepoetic experience o f Salvatore Quasimodo through the panoramicevolution of his works, in which is underlined a series of antinomies:transparency-shadow, word-occurencet ownership-separability, innerlandscape- originary soil. In each one of these cases exists the firmconviction that poetry is an ethical and an esthetical matter a messageof companionship and clarity ofmen ’s destiny.